Prisoner of the state : the secret journal of Premier Zhao Ziyang - Zhao, Ziyang; Bao, Pu, 1967?-; Chiang, Renee; Ignatius, Adi.; MacFarquhar, Roderick (New York : Simon & Schuster, 2009)
Gives readers a front row seat to the secret inner workings of China's government. It is the story of Premier Zhao Ziyang, who tried to stop the Tiananmen Square massacre in 1989, and was dethroned for his efforts.
Koleksi Sumbangan Dr Mohd Nasrin.
Keywords: Zhao, Ziyang; Prime ministers -- China -- Biography; Political prisoners -- China -- Biography; Statesmen -- China -- Biography; China -- Politics and government -- 1976-2002.; China -- History -- Tiananmen Square Incident, 1989.